PENGARUH KETERBATASAN AKSES TEKNOLOGI TERHADAP MOTIVASI SISWA DALAM PEMBELAJARAN DI PEDESAAN - Istiqomah, Istiqomah; Ramadhani, Chairunisa Mardiah; Safitri, Sani; Pamulaan, Alif Bahtiar (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
This article discusses ?The Effect of Limited Access to Technology on Student Motivation in Rural Learning?. The purpose of this article is to find out the challenges faced by rural learning in the influence of limited access to technology on student motivation and solutions in the influence of limited access to technology on student motivation in rural areas. The research method used in making this article is a qualitative descriptive method by explaining the effect of limited access to technology on student motivation in rural learning. Digital technology has a great influence on student motivation, especially in rural areas where access to technology or training is limited. Students who do not have digital skills, they tend to feel difficulty and frustration in utilizing technology for learning, which can reduce interest in learning. In light of this, it is imperative for the relevant government to develop effective training programs to improve digital literacy among both students and adults. By doing so, they will be more confident when facing technological challenges in learning, which will increase student motivation and success